Effect of fertilizer inputs on productivity and herbage quality of native pasture in degraded tropical grasslands - Bedaso, N.H.; Bezabih, Melkamu; Zewdu, T.; Adie, Aberra; Khan, N.A.; Jones, Christopher S.; Mekonnen, Kindu; Woldemeskel, Endalkachew (Wiley, 2022)
The practice of applying fertilizer inputs on an unimproved natural pasture is limited in tropical grasslands. A study was conducted to evaluate the response of degraded natural pasturelands in terms of species composition, forage yield, and quality to the application of different types of fertilizer. The study was conducted in two districts in the central Rift Valley of Ethiopia with contrasting agroecologies. The treatments were control (no application of fertilizer), commercial fertilizer (50 kg urea ha–1 and 100 kg diammonium phosphate [DAP] ha–1), cattle manure (7.5 t ha–1), wood ash (3 t ha–1), and lime (7.5 t ha–1). Soil physical properties were not altered following application of the treatments, but chemical properties, including soil pH (P < .01), electroconductivity (EC) (P < .001), total nitrogen (TN), and P (P < .001) were affected. Soil TN increased from 0.11 to 0.32% following the application of cattle manure. The pH increased from 5.9 to 7.3 with wood ash application. Herbage dry matter (DM) yield increased (P < .001) from 1.88 to 6.65 t ha–1 with chemical fertilizer. The herbage crude protein content increased (P < .01) from 96 to 157 g kg–1 with manure application. On the other hand, the neutral detergent fiber tended to decrease (P < .05) following manure application. Partial cost‐benefit analysis indicated a positive economic gain from the direct sale of pasture hay for all treatments except for lime. The results indicated that fertilizer inputs offer feasible options to improve pasture productivity and enable rural farmers to benefit from their land resources.